Comprehension and selective visual attention in play-calling signage in NCAA Division 1 football: A comprehensive literature review - Brown, C.; Holland, A.; Delarosa, J.; Doude, M.; Reimann, W.; Rath, T.; Piroli, A. (International Journal of Kinesiology & Sports Science, 2020)
Background: The huddle in American college football has been replaced by hand-signals, play-cards, and other forms of nonverbal communication to deliver information from the sidelines to the field. These communication methods serve a dual-purpose of capturing the student-athletes` attention while perplexing the opposition. Objective: The purpose of this study is to apply cognitive engineering concepts toward the improvement of signage and play-calling such that coaches can more effectively transmit information to players on the field during competitions. Methods: This comprehensive literature review investigates strategies for successful visual play-calling systems in sports communication. Collaboration occurred with a National Collegiate Athletic Association (NCAA) Division 1 football coaching staff to understand communication processes on field. Existing literature related to visual language processing, selective attention, and signal comprehension were compiled for recommendations. Results: Research findings suggest positive correlations between speed, clarity, and simplicity of signage in addition to effective sideline communication. The results of this review can be used to develop guidelines that increase the accuracy and speed of play-calling during games, such as clearly designed imagery and simplified play calls; coaches may establish strategies that are consistently understood by student-athletes. Conclusion: In addition to the findings, this study also identifies visual communication methods and mediums that can be used in any sport or work field where transmitting and comprehending information from a distance is critical for task completion.